2021
DOI: 10.5765/jkacap.210009
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Association between Empathy and Brain Structure in Attention-Deficit/Hyperactivity Disorder

Abstract: Objectives To investigate the relationship between brain structure and empathy in early adolescents with attention-deficit/hyperactivity disorder (ADHD). Methods Nineteen early adolescents with ADHD and 20 healthy controls underwent 3T MRI. All the participants were assessed for different aspects of empathy using measures including the Interpersonal Reactivity Index and Empathy Quotient. Cortical thickness and subcortical structural volume based on T1-weighted scans wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In ADHD, there were six ADHD datasets that recruited medication-naïve patients [ 44 ] or patients who discontinued medications before MR scans [ 39 , 40 , 43 , 45 ]. Three ADHD datasets [ 41 , 42 , 46 ] used medicated patients and one dataset did not clearly indicate the medication status [ 47 ]. With regard to comorbidities, six ADHD datasets recruited pure ADHD patients [ 39 , 41 , 43 46 ] while four ADHD datasets reported that some patients had comorbid conduct disorder, oppositional defiant disorder [ 40 , 45 ], epilepsy [ 42 ], and behavioral and anxiety related disorder [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ADHD, there were six ADHD datasets that recruited medication-naïve patients [ 44 ] or patients who discontinued medications before MR scans [ 39 , 40 , 43 , 45 ]. Three ADHD datasets [ 41 , 42 , 46 ] used medicated patients and one dataset did not clearly indicate the medication status [ 47 ]. With regard to comorbidities, six ADHD datasets recruited pure ADHD patients [ 39 , 41 , 43 46 ] while four ADHD datasets reported that some patients had comorbid conduct disorder, oppositional defiant disorder [ 40 , 45 ], epilepsy [ 42 ], and behavioral and anxiety related disorder [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three ADHD datasets [ 41 , 42 , 46 ] used medicated patients and one dataset did not clearly indicate the medication status [ 47 ]. With regard to comorbidities, six ADHD datasets recruited pure ADHD patients [ 39 , 41 , 43 46 ] while four ADHD datasets reported that some patients had comorbid conduct disorder, oppositional defiant disorder [ 40 , 45 ], epilepsy [ 42 ], and behavioral and anxiety related disorder [ 47 ]. It should be noted that patients with a history of cannabis use [ 43 ] were not considered as a comorbidity in the current study.…”
Section: Resultsmentioning
confidence: 99%
“… Encompassed Baribeau et al (2019), Bitter et al (2011), Kim et al (2022), Lee et al (2021), Tajima‐Pozo et al (2018), and Wang et al (2018). …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the ES was not adjusted (Hedges's g = 0.43). In contrast, using volume-based measurement, the combined results from 10 data sets demonstrated a nonsignificant difference between participants with ADHD and their controls (Hedges' g = −0.01, p = .94, Figure 2; Baribeau et al, 2019;Bitter et al, 2011;Filipek et al, 1997;Hoogman et al, 2017;Kim et al, 2022;Lee et al, 2021;Tajima-Pozo et al, 2018;Wang et al, 2018). The mega data from Hoogman et al (2017) were divided into three data sets, namely children, adolescents, and adults.…”
Section: Quantitative Data Analysismentioning
confidence: 97%